2017
DOI: 10.1002/pros.23364
|View full text |Cite
|
Sign up to set email alerts
|

Blinded review of archival radical prostatectomy specimens supports that contemporary Gleason score 6 prostate cancer lacks metastatic potential

Abstract: Unbiased pathologist review of archival RP specimens supports absent metastatic potential for contemporarily defined GS6 CaP. Reduced postoperative monitoring is appropriate for pGS6, but may require pathology review to confirm absent Gleason pattern 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…TMA demonstrated that the general expression of CEMIP in PCa tissue was substantially higher compared with that in their pericarcinous counterparts. Surprisingly, in the present work, the expression of CEMIP did not seem to be positively statistically correlated with GS, and some reports also observed that the current GS system might occasionally fail to represent-as an indicator-PCa progression and expression of certain oncogenes (31)(32)(33). Of note, CEMIP was indeed more intensively expressed in intermediate-and high-risk patients compared with their low-risk counterparts (data not shown).…”
Section: Discussioncontrasting
confidence: 79%
“…TMA demonstrated that the general expression of CEMIP in PCa tissue was substantially higher compared with that in their pericarcinous counterparts. Surprisingly, in the present work, the expression of CEMIP did not seem to be positively statistically correlated with GS, and some reports also observed that the current GS system might occasionally fail to represent-as an indicator-PCa progression and expression of certain oncogenes (31)(32)(33). Of note, CEMIP was indeed more intensively expressed in intermediate-and high-risk patients compared with their low-risk counterparts (data not shown).…”
Section: Discussioncontrasting
confidence: 79%
“…Evolving data have suggested that true Gleason score 6 prostate cancer does not have metastatic potential. 21 Although we did find men with Gleason score 6 prostate cancer at baseline in the metastatic disease cohort, we were not able to perform a contemporary pathologic review and many of these cases would likely be upgraded based on changes to Gleason scoring after the International Society of Urological Pathology report of 2005. 22 In addition, baseline risk in the current study was based on biopsy Gleason score and higher-grade tumors within the prostate may be missed after standard 12-needle core prostate biopsy.…”
Section: Discussionmentioning
confidence: 92%
“…22 Beginning with the fourth TRUS biopsy, PSA kinet- Importantly, a review of Gleason score 6 radical prostatectomy (RP) specimens confirmed the absence of metastatic potential in these lesions. 25 1,3,9 Only 30% of men on AS in the PRIAS (Prostate Cancer Research International Active Surveillance) series followed for more than 4 years had undergone all of the biopsies recommended by study protocol. 26 In the future, genomic testing and MRI will play greater roles in patient selection and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Tosoian et al reported that in favorable risk prostate cancer, the risk of progression to a lethal phenotype is low (0.4%) in the decade following diagnosis 9 . Importantly, a review of Gleason score 6 radical prostatectomy (RP) specimens confirmed the absence of metastatic potential in these lesions 25 . Following RP with Gleason score 6 histology a 0.2% cancer death rate was reported.…”
Section: Discussionmentioning
confidence: 99%